Italian Law on "medically assisted procreation": a biojuridical reading. - Palazzani, Laura (Medicina e Morale, 2004)
The article analyses the recent Italian law on medical assisted reproduction from the point of view of the relation between bioethics and law, paying particular attention on the discussion of the different and opposing biojuridical models, that is models of conceiving the role and function of law and legislation in bioethics (the liberal model of "neutrality" and the model of justice as "minimal ethics"). The article critically analyses (from the point of view of the philosophy of law) the principal topics of the law (the subjectivity of the human embryo and the role of family) in order to point out the themes which are or not correspondent to the essential significance of law and justice.